Developmental changes in mental rotation ability and visual perspective-taking in children and adults with Williams syndrome - Hirai, Masahiro; Muramatsu, Yukako; Mizuno, Seiji; Kurahashi, Naoko; Kurahashi, Hirokazu; Nakamura, Miho (Frontiers in Human Neuroscience, 2013)
Williams syndrome (WS) is a genetic disorder caused by the partial deletion of chromosome 7. Individuals with WS have atypical cognitive abilities, such as hypersociability and compromised visuospatial cognition, although the mechanisms underlying these deficits, as well as the relationship between them, remain unclear. Here, we assessed performance in mental rotation (MR) and level 2 visual perspective taking (VPT2) tasks in individuals with and without WS. Individuals with WS obtained lower scores in the VPT2 task than in the MR task. These individuals also performed poorly on both the MR and VPT2 tasks compared with members of a control group. For the individuals in the control group, performance scores improved during development for both tasks, while the scores of those in the WS group improved only in the MR task, and not the VPT2 task. Therefore, we conducted a second experiment to explore the specific cognitive challenges faced by people with WS in the VPT2 task. In addition to asking participants to change their physical location (self-motion), we also asked them to adopt a third-person perspective by imagining that they had moved to a specified location (self-motion imagery). This enabled us to assess their ability to simulate the movement of their own bodies. The performance in the control group improved in both the self-motion and self-motion imagery tasks and both performances were correlated with verbal mental age. However, we did not find any developmental changes in performance for either task in the WS group. Performance scores for the self-motion imagery task in the WS group were low, similar to the scores observed for the VPT2 in this population. These results suggest that MR and VPT2 tasks involve different processes, and that these processes develop differently in people with WS. Moreover, difficulty completing VPT2 tasks may be partly because of an inability of people with WS to accurately simulate mental body motion.